TEOLOGI FEMINISME PERSPEKTIF AMINA WADUD: INTEGRASI LOGIKA NORMATIFITAS DAN HISTORISITAS (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2013)
Study on feminism is an important study in the contemporary era. It is important, either from the supporting context, or from the opponent. Seen from the logic of normativity, the feminist study got a clear negation. However, when viewed from the logic of the historicity, the feminist studies got a good place. The complexity of social reality forces the researchers to examine more on feminist issues. Through integrating two methods of logic–the logic of normativity and the logic of the historicity–feminist studies are considered important to be discussed in order to reconcile the two logics.